A Study on the Effect of Exercise Prescription on Scoliosis in Adolescents - Guifang Liu; Yonglei Liu; Haoyuan Li *, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In order to understand the efficacy of a scoliosis exercise prescription, it is essential to understand the risk factors associated with this malady. The purpose of this quantitative study was to determine whether or not prescribed exercise would decrease the likelihood of developing scoliosis by influencing one or more sub-clinical risk factors involved with the condition. Before and after an adolescent participated in an exercise prescription for two months, nutritional intake and other health parameters were measured. Scoliosis incidence was determined in order to assess whether or not prescribed exercises reduce incidence. The study found that preprogramed exercises significantly reduced incidence by as much as 44% on average as compared to a non-prescribed condition (p < .001). Additionally, the longer the participant was involved in the regimen, the greater the reduction. The study also found that a non-prescribed condition (no exercise) did not yield any significant reduction level in incidence. The finding of this study supports previous research, which concluded that exercise prescription can be an effective scoliosis treatment option in adolescents with subclinical scoliosis.